PENGARUH STRATEGI DIRECT INSTRUCTION DALAM PEMBELAJARAN IPAS TENTANG “WARISAN BUDAYA” TERHADAP HASIL BELAJAR SISWA KELAS V - saputra, tirta; hatim, magdad; abdullah, bz septieyawan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of Direct Instruction strategy in learning Natural and Social Sciences (IPAS) on the material "Cultural Heritage" on the learning outcomes of fifth grade elementary school students. Direct Instruction Strategy is a learning model that focuses on delivering material directly, systematically, and structured by teachers, which is expected to improve is a learning model that focuses on delivering material directly, systematically, and structured by teachers, which is expected to improve students' understanding optimally. This study uses a quantitative approach with a quasi-experimental method (quasi-experimental). The subjects of the study were fifth grade students at SD Negeri 160 Palembang consisting of experimental classes and control classes. Data collection techniques were carried out through learning outcome tests given before (pretest) and after (posttest) treatment. The results of data analysis showed that there was a significant increase in learning outcomes in students who were taught using the Direct Instruction strategy assisted by learning videos compared to students who learned using lecture or conventional methods. Thus, it can be concluded that the Direct Instruction strategy has a significant effect on student learning outcomes in the material "Cultural Heritage".